2009
DOI: 10.1186/1471-2407-9-122
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of folate, vitamin B6, and vitamin B12, genetic polymorphism of related enzymes, and risk of breast cancer: a case-control study in Brazilian women

Abstract: BackgroundSeveral studies have determined that dietary intake of B vitamins may be associated with breast cancer risk as a result of interactions between 5,10-methylenetetrahydrofolate reductase (MTHFR) and methionine synthase (MTR) in the one-carbon metabolism pathway. However, the association between B vitamin intake and breast cancer risk in Brazilian women in particular has not yet been investigated.MethodsA case-control study was conducted in São Paulo, Brazil, with 458 age-matched pairs of Brazilian wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 43 publications
5
51
1
7
Order By: Relevance
“…Nonetheless, an increased BC risk, in subjects with a combination of a low dietary intake of one-carbon metabolism vitamins and the MTHFR 677TT alleles, was shown in a number of earlier studies in different populations, which is in agreement with our findings (Alshatwi 2010;Chen et al 2005;Gao et al 2009;Lee et al 2004;Maruti et al 2009;Shrubsole et al 2004). Interestingly, other studies evidenced a high BC risk in individuals with the variant MTHFR 677TT genotype and increased intake of folate (Ericson et al 2009;Ma et al 2009a;Stevens et al 2007). With respect to the MTHFR 1298A[C SNP, a study found that females with the MTHFR 1298AC and MTHFR 1298CC genotype and low dietary folate consumption, had an increased BC risk, results which are similar to our results (Ma et al 2009a).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Nonetheless, an increased BC risk, in subjects with a combination of a low dietary intake of one-carbon metabolism vitamins and the MTHFR 677TT alleles, was shown in a number of earlier studies in different populations, which is in agreement with our findings (Alshatwi 2010;Chen et al 2005;Gao et al 2009;Lee et al 2004;Maruti et al 2009;Shrubsole et al 2004). Interestingly, other studies evidenced a high BC risk in individuals with the variant MTHFR 677TT genotype and increased intake of folate (Ericson et al 2009;Ma et al 2009a;Stevens et al 2007). With respect to the MTHFR 1298A[C SNP, a study found that females with the MTHFR 1298AC and MTHFR 1298CC genotype and low dietary folate consumption, had an increased BC risk, results which are similar to our results (Ma et al 2009a).…”
Section: Discussionsupporting
confidence: 82%
“…In other studies, however, no statistically significant association between dietary intake and MTHFR polymorphisms in BC was found (Le Marchand et al 2004;Lissowska et al 2007;Liu et al 2013;Ma et al 2009b;Naushad et al 2011;Shrubsole et al 2006;Xu et al 2007). This discrepancy may be due to differences in several factors including ethnic background, small sample sizes, low allele frequencies or different dietary exposures (Chou et al 2006;Ma et al 2009a;Stevens et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations